A ditadura militar chilena como um ponto de inflexão na trajetória da Comissão Interamericana de Direitos Humanos - Delarisse, Thaís Maria (2018)
This paper aims to present the political and institutional trajectory of the Inter-American Commission on Human Rights (IACHR), from its origin in 1959 until 1990. It is argued that during the 1970s the Commission went through an inflection point, from which it gained greater notoriety and was projected as a relevant and accredited actor in the area of human rights, as a result of its investigation into the human rights situation in Chile during the government of General Augusto Pinochet. This process resulted in the institutional development of the body, as well as facilitated the placing on the international agenda of elements such as the right to truth, justice, and reparation that later added to the IACHR's definition of transitional justice. The institutional decision to proceed with the investigation into Chile was possible because of a concert of political dynamics and disputes observed in the internal and external environment of the body, which provided political opportunities for the institution's performance.